Study on Association of Pentraxin 3 and Diabetic Nephropathy in a Rat Model - Xuehai Chen; Jiao Luo; Minmin Wu; Zhuo Pan; Yue Xie; Hongwei Wang; Bicheng Chen; Hong Zhu (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a serious microvascular complication of diabetes. Compared with other therapies for diabetic patients, islet transplantation can effectively prevent and reverse diabetes-induced microvascular disease, such as diabetic retinopathy and nephropathy. PTX3 is the only long pentraxin that can be detected in renal tissue. In this study, we investigated the expression of PTX3 when early DN was reversed after islet transplantation. Methods. Diabetes was induced in rats by injecting streptozotocin (STZ). Twelve weeks later, the diabetic rats were divided into 2 groups: the islet transplantation group (IT) and the diabetic nephropathy group (DN). Renal injury, renal function, and the expression of PTX3 in the plasma and the kidneys were assessed with urinalysis, immunohistochemical staining, and Western blot, respectively. Results. The expression of PTX3 in the kidney was significantly decreased in the DN group but increased in the IT group because of the reversal of DN. Conclusions. Our data showed that the level of PTX3 in renal tissue is closely related to renal injury in DN. This may be used to quantify the extent of renal injury in DN, provide a potential early indicator of renal tubular injury in early DN patients, and assess DN clinical progression.